Perancangan Dudukan Outboard Engine sebagai Sarana Penunjang pada Laboratorium Outboard Engine Politeknik Perkapalan Negeri Surabaya - Aloysius Yudhistira Adi Nugraha; George Endri Kusuma; Widya Emilia Primaningtyas (Proceedings Conference On Design Manufacture Engineering And Its Application, 2021)
The outboard motor mount is an important piece of equipment when building an outboard motor workshop or laboratory. The outboard motor mount is needed because it is not possible to learn about the motor components with the motor attached to the hull of the boat. Therefore, it is necessary to design an outboard motor holder that fits the lot size and can be moved to facilitate the testing of the outboard motor in the test pool located outside the laboratory building. The design is carried out by making 3 models of the seat frame using the Ulrich method and Finite Element Analysis to analyze the strength of each concept. Rapid Upper Limb Assessment is used to analyze the ergonomic aspects of the three concepts. Based on Finite Element Analysis, it is known that the safety factors of concept 1, 2 and 3 are 1,985, 1,689 and 1,860 respectively. The results of the Rapid Upper Limb Assessment analysis show that the three concepts have a final score of 3. Based on the priority scale table with the criteria of evaluating manufacturing costs, ergonomics, flexibility, mass, ease of manufacture and ease of assembly, score concept 1,2 and 3 are 24%, 25% and 29% repectively. From this value, the selected concept is concept 3 as shown in the detailed drawing attachment A.